10-year Portuguese football strategic plan: sustainable growth - the rise of virtual football - Graveto, João Pedro Da Silva (2022)
This analysis serves as a complement to the 10-year Portuguese Football Strategic Plan conducted in Partnership with FPF and Deloitte. After measuring the impact of fan engagement, women’s football, academic football, broadcasting rights, and international exposure, this report was directed towards the emerging rise of the gaming and eSports industry. A perspective was given towards the sector globally, introducing a detailed analysis of the Portuguese landscape. Overall, the aim was to understand how to enhance the current status of the national virtual football panorama by recommending strategies to increase its attractiveness.